A new species of Cleistanthus (Euphorbiaceae) from Andaman Islands - Balachandran, N.; Gastmans, W. F.; Chakrabarty, T. (Rheedea, 2010)
A new species, Cleistanthus andamanicus N. Balach., Gastmans et Chakrab. is described from the Andaman Islands, India.